Results and lessons learned from a prevention of weight gain program for low-income overweight and obese young mothers: Mothers In Motion - Mei-Wei Chang; Roger Brown; Susan Nitzke (BMC, 2017)
Abstract Background Mothers In Motion (MIM), a community-based lifestyle behavioral intervention, was designed and conducted to help low-income overweight and obese young mothers prevent further weight gain via promotion of stress management, healthy eating, and physical activity. This paper presents intervention effect on body weight (primary outcome) and summarizes lessons learned. Methods Participants (N = 612) were recruited from 7 Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) offices in Michigan and were individually randomized to an intervention n= 410) or a comparison (n =202) group (2: 1 ratio). During the 16-week intervention, intervention participants watched theory-based culturally sensitive videos (in DVD format) featuring peers from the target audience to learn skills for managing stress, eating healthier, and being more physically active. They also dialed into peer support group teleconferences to enhance skills learned in the videos and increase motivation for lifestyle behavioral changes. Body weight, the primary outcome, was measured at baseline, immediately after the 16-week intervention, and 3 months after the 16-week intervention. Intervention effect was tested via general linear mixed model for repeated measures, using baseline measures as adjusting covariates. Results At baseline, the mean age of the participants was 28.5 ± 5.0 years (intervention: 28.4 ± 5.0, comparison: 28.9 ± 5.0); the mean body weight was 190.2 ± 1.4 lbs (intervention: 191.8 ± 30.0, comparison: 188.5 ± 29.1); and the mean body mass index (BMI) was 32.2 ± 4.4 (intervention: 32.2 ± 4.4, comparison: 31.7 ± 4.2). Of sample, 64.7% were obese. At 3 months after the 16-week intervention, no significant weight differences were found between the intervention (188.3 ± 10.6 lbs, BMI: 31.6 ± 1.8) and comparison groups (187.7 ± 10.6 lbs, BMI: 31.53 ± 1.8) when controlling for baseline body weight. Conclusions This lifestyle behavioral intervention that focused on stress management, healthy eating and physical activity was not effective in helping low-income overweight and obese young mothers prevent further weight gain. Trial registration Clinical Trials NCT01839708 . This trial was registered retrospectively on February 28, 2013.